2017
DOI: 10.1111/hojo.12199
|View full text |Cite
|
Sign up to set email alerts
|

The Context and Impact of Being Wrongly Accused of Abuse in Occupations of Trust

Abstract: In recent years, there has been rising concern that allegations of sexual abuse, particularly non‐recent abuse, have not received an appropriate response. From this has emerged a new determination to correct past and prevent further injustices, with police operations focusing considerable resources on the identification and prosecution of child abusers. Police and other services have reached out to encourage reporting, and developments in the trial process related to the rules of evidence have eroded due proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…Commonly, social networks, friendships and relationships appeared to break down after individuals were wrongfully accused. In the Burnett et al 27 and Hoyle et al 29 study, 27/30 participants reported a fractured social network, 17/30 reported a strain on intimate relationships and 8/30 reported a strain on relationships with children or grandchildren. Additionally, many reported feeling 'forced out' of friendships.…”
Section: Relationships With Othersmentioning
confidence: 96%
See 4 more Smart Citations
“…Commonly, social networks, friendships and relationships appeared to break down after individuals were wrongfully accused. In the Burnett et al 27 and Hoyle et al 29 study, 27/30 participants reported a fractured social network, 17/30 reported a strain on intimate relationships and 8/30 reported a strain on relationships with children or grandchildren. Additionally, many reported feeling 'forced out' of friendships.…”
Section: Relationships With Othersmentioning
confidence: 96%
“…34,35,41,42 PTSD. Several papers also noted probable PTSD in those wrongfully accused: 17/30 participants in the study reported by Burnett et al 27 and Hoyle et al 29 ; 12/18 participants in the Grounds 15 34 also noted that many of the participants in their qualitative study reported experiencing PTSD.…”
Section: Psychological and Physical Healthmentioning
confidence: 96%
See 3 more Smart Citations